Theranostic Nanomedicines for the Treatment of Cardiovascular and Related Diseases: Current Strategies and Future Perspectives - Manners, Natasha; Priya, Vishnu; Mehata, Abhishesh Kumar; Rawat, Manoj; Mohan, Syam; Makeen, Hafiz A.; Albratty, Mohammed; Albarrati, Ali; Meraya, Abdulkarim M.; Muthu, Madaswamy S. (MDPI, 2022)
Cardiovascular and related diseases (CVRDs) are among the most prevalent chronic diseases in the 21st century, with a high mortality rate. This review summarizes the various nanomedicines for diagnostic and therapeutic applications in CVRDs, including nanomedicine for angina pectoris, myocarditis, myocardial infarction, pericardial disorder, thrombosis, atherosclerosis, hyperlipidemia, hypertension, pulmonary arterial hypertension and stroke. Theranostic nanomedicines can prolong systemic circulation, escape from the host defense system, and de-liver theranostic agents to the targeted site for imaging and therapy at a cellular and molecular level. Presently, discrete non-invasive and non-surgical theranostic methodologies are such an advancement modality capable of targeted diagnosis and therapy and have better efficacy with fewer side effects than conventional medicine. Additionally, we have presented the recent updates on nanomedicine in clinical trials, targeted nanomedicine and its translational challenges for CVRDs. Theranostic nanomedicine acts as a bridge towards CVRDs amelioration and its management.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: atherosclerosis; cardiovascular disease; personalized therapy; pharmaceutical nanomedicine; targeted delivery; atherosclerosis; cardiovascular disease; personalized therapy; pharmaceutical nanomedicine; targeted delivery; acylcarnitine; amiodarone; andrographolide; apolipoprotein E; atorvastatin; calcium channel blocking agent; captopril; carvedilol; CD40 ligand; cerium oxide nanoparticle; chitosan; curcumin; cytochrome P450 3A4; docosahexaenoic acid; doxorubicin; fasudil; ginsenoside Rg 1; gold nanoparticle; graphene oxide; hyaluronic acid; icosapentaenoic acid; iloprost; imatinib; interleukin 8; ivabradine; lisinopril; magnetic nanoparticle; monocrotaline; nicorandil; paclitaxel; perfluoropentane; pioglitazone; pitavastatin; prednisolone; quantum dot; reactive oxygen metabolite; sildenafil; simvastatin; streptokinase; tirofiban; urokinase; verapamil; angina pectoris; anticoagulant therapy; antithrombotic activity; apoptosis; atherosclerosis; atherosclerotic plaque; capillary density; cardiovascular disease; cell migration; cell proliferation; cerebrovascular accident; clinical outcome; clinical trial (topic); coronary artery blood flow; drug delivery system; fluorescence imaging; heart failure; heart infarction; histopathology; human; hyperlipidemia; hypertension; myocarditis; neuroprotection; oxidative stress; personalized medicine; photothermal therapy; pulmonary hypertension; radiography; Review; systemic circulation; theranostic nanomedicine; thrombosis